Perioperative nursing of an osteoporosis patient undergoing second operation for Stanford type A aortic dissection (合并骨质疏松的Stanford A型主动脉夹层二次手术患者的围术期护理) - JIN Fangfang (金芳芳); SU Yunyan (苏云艳); HU Yuexiu (胡岳秀); WU Mengya (伍梦雅) (中西医结合护理)
This paper summarized the perioperative nursing management of an osteoporosis patient undergoing second operation for Stanford type A aortic dissection. An individualized health assessment and interventions of controlling of heart rate and blood pressure were carried out before operation. The safe management strategies and medication care were implemented for osteoporosis. Catheter was placed after surgery and coordinated management of respiratory tract was carried out. Postoperative interventions also included nursing of neurological symptoms and enteral nutrition support. (本文总结1例合并骨质疏松的Stanford A型主动脉夹层二次手术患者的围术期护理体会。术前通过对患者进行个性化评估, 给予控制心率、血压, 骨质疏松症患者的安全管理及用药护理; 术后患者二次插管, 通过呼吸道的护理, 维持有效循环, 给予神经系统护理、肠内营养支持等。)